Effects of Age, Gender and Education Level on Financial Literacy Level (Study of Vocational School Teachers in Padang City) (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
This research is motivated by the low financial literacy in Indonesia. The research objective was to determine the factors that affect the level of financial literacy. The research subjects were teachers of productive majors at SMK in Padang City. Productive teacher financial literacy was measured by a questionnaire. The Feasibility Test of the Regression Model is determined by the Hosmer and Lemeshow's Goodness of Fit Test, Overall Model Fit. The research hypothesis was tested using binary logistic regression. The results showed that: gender factors, age, and length of work had a significant effect on financial literacy, while education and income factors did not affect the financial literacy of teachers in productive majors in SMK Se Padang City.Keywords: Financial Literacy, Gender, Age, Length of Work, Education Level, Income Level